PETS AND DIVORCE - Stojanovic, Natasa (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2026)
Divorce is a relatively frequent phenomenon the consequences of which affect not only spouses but also their offspring, other family members, wider social community, as well as pets owned by such married couple. The Family Law of the Republic of Serbia, though containing numerous rules, being of substantive law and procedural law character, on a dissolution of marriage and its consequences, it speaks nothing about legal fate of the divorced spouses’ pets in the event they do not agree on who will take care of them once the marriage has been terminated. Should a pet be treated, during divorce, as a movable property, which has been a predominant stand in Serbian judicial practice for decades, or as a living being that, like a human being, can feel pain, suffering, fear, stress, and panic, which is explicitly stipulated by the Law on Animal Welfare? In the research process, using primarily comparative and legal, but also legal and dogmatic, normative and legal, and historical and legal methods, we have been seeking an answer to the question posed. Through a prism of legal solutions, judicial stands and theoretical concepts in French, Russian, Spanish and American laws, we shed light on contemporary trends regarding the legal fate of pets after the divorce of their owners. This research has a dual purpose. On one hand, the aim is to propose adequate solutions to the Serbian legislator that should facilitate making the divorce as painless as possible for the spouses themselves, but also for their pets. On the other hand, the number of abandoned pets as a result of the termination of marriage through divorce should be reduced by this proposed legal mechanism precisely.